The Penland book of handmade books : master classes in bookmaking techniques. - Penland School of Crafts (New York : Lark ; Lewes : GMC Distribution [distributor], 2008)
The Penland School of Crafts is a leading centre of craft education in North Carolina. With this text student bookbinders will discover technical and inspirational resources from the masters that will carry their craft to new levels.
Daniel Essig : technique : books as sculpture -- Eileen Wallace : technique : simplified binding -- Steve Miller : technique : the reduction linoleum cut -- Carol Barton : technique : pop-up structures -- Susan E. King : technique : content and intent -- Hedi Kyle : technique : folded structures -- Barbara Mauriello : technique : box construction -- Dolph Smith : technique : sculpture as books -- Jim Croft : technique : wood covers and metal clasps -- Julie Leonard : technique : stiff leaf structures.
Originally published: 2004.
Includes index.
Keywords: Bookbinding -- Handbooks, manuals, etc; Books -- Handbooks, manuals, etc; Bookbinding -- Study and teaching